Partnership as an Alternative Model for Empowering Fishers in the Processed Food Industry Made from Marine Fish - Siti Malikhatun Badriyah; R. Suharto; Retno Saraswati; Muhammad Haidar Fakhri Allam; Kornelius Benuf (Universitas Ahmad Dahlan, 2021)
Introduction to the Problem: This study discusses cooperation between various parties that are mutually beneficial, both the government, large business actors, and small business actors, in this case, fishermen.Purpose/Objective of the Study: This research aims to maximize the management of fisheries potential in Indonesia and provide alternatives to fishermen out of the problems they face.Design/Methodology/Approach: This study uses a mixed-method, which combines quantitative and qualitative research.Findings: The results showed that by looking at the background as well as the potential and weaknesses of the fishing community, the business partnership model could be an alternative to empowering the fishing community in developing the processed food industry made from marine fish. The legal relationship of the parties in this business partnership is based on the partnership agreement.Paper Type: Research Article